CORPUS LINGUISTICS RESEARCH: ANALYZE THE USE OF INFLECTIONAL MORPHEME IN “THE FAULT IN OUR STARS” NOVEL BY JOHN GREEN - Averedinta Delia Trisnanda; Lilia Indriani (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2021)
Novels are timeless. From teenagers to adults, they still choose a novel to spend time with, entertain themselves before bedtime, or even make a hobby. One of the most important yet unseen is the inflectional morpheme. The inflectional morpheme is a morpheme that does not alter the sense of the word. It is used to identify the type of words used in the text. This makes inflectional morpheme an essential ingredient in writing. Inflectional morpheme consists of suffixes added at the end of words that do not change either part of speech or meaning. It gives extra grammatical information about the already existing meaning of the word (Bauer, 1988:12). The use of inflectional morpheme in a novel is important. One of the novels with an inflectional morpheme is John Green titled "The Fault in Our Stars." The most remarkable novel by John Green describes the romantic relationship between two teenagers that have cancer. The tragic romantic journey between Hazel Grace and Augustus Waters. This research aimed to analyze the inflectional morpheme in the novel. This research is used descriptive qualitative. It is hoped that this article may help students to learn more about the types of inflectional morpheme and the function of each inflectional morpheme.